(untitled) (Sustainability in Debate, 2020)
The intensification of agricultural production and its impact has been widely discussed around the world. Agricultural diversification is a possible path to promote sustainability in agriculture, considering ecological and socioeconomic aspects. Thus, this paper aims to develop an indicator that could assess the agricultural diversification of the municipalities of Minas Gerais, to understand the dynamics of agriculture in the state. Our results show that most of the municipalities (76%) presented a "high" or "very high" diversification, and it can be explained by the strong presence of family farming. However, the share of the gross domestic product (GDP) of these municipalities relative to agriculture activity is relatively low, highlighting that economic sustainability has not been fully achieved yet. In addition to the producer’s interest in increasing agricultural diversification, it is important to ensure a rural development public policy fostering diverse agricultural production systems aligned with environmental sustainability standards.